1978
DOI: 10.2172/6643283
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and toxicological assessment of an external heat (burn) test of the 105MM cartridge, APFSDS-T, XM-744

Abstract: This repon was prepared 3s an account of work sponsored by the Unired 5tates Government. Neither the Uniied States nor the Depanment d Energ)', nor any of heir employ-, nor any of their contractors. subcontractors, or their employeer. makes any warranty. express or implied, or assumes any legal liability or reponsibiliry for the accuracy, completeness or uwfulnmr of any ~nformation, apparatus, p d u a or process disclosed, or represents thar its use would not intrrnge pr~vately owned rights. The views. opinion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous experience in the burning and fragmentation of XM774 depleted uranium ammunition indicated that envelopement in a hot fire would not result in an airborne release of a depleted uranium aerosol . In particular, the external heat test performed on the XM774 ammunition in October 1977 at Frenchman Flat, resul t ed in the cartridges being blown clear of the fire by propellant ignition , before oxidation could occur (Gilchrist, Parker, Mishima 1978) . A factor that appeared to be critical for the XM774 ammunition to be blown clear of the fire was the design of the cartridge case .…”
Section: Introductionmentioning
confidence: 99%
“…Previous experience in the burning and fragmentation of XM774 depleted uranium ammunition indicated that envelopement in a hot fire would not result in an airborne release of a depleted uranium aerosol . In particular, the external heat test performed on the XM774 ammunition in October 1977 at Frenchman Flat, resul t ed in the cartridges being blown clear of the fire by propellant ignition , before oxidation could occur (Gilchrist, Parker, Mishima 1978) . A factor that appeared to be critical for the XM774 ammunition to be blown clear of the fire was the design of the cartridge case .…”
Section: Introductionmentioning
confidence: 99%